2020
DOI: 10.1177/0003134820939928
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Binder Utilization in Combat Casualties: Does It Matter?

Abstract: Introduction The purpose of this study was to evaluate the utilization of pelvic binders, the proper placement of binders, and to determine any differences in blood product transfusions between combat casualties with and without a pelvic binder identified on initial imaging immediately after the injury. Methods We conducted a retrospective review of all combat-injured patients who arrived at our military treatment hospital between 2010 and 2012 with a documented pelvic fracture. Initial imaging (X-ray or compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…However, one study found that with very low certainty of evidence, patients with a PCCD placement in pre-hospital setting could signi cantly receive less blood transfusions (OR 0.63, 95%CI 0.41-0.95). A similar nding was found in other two studies with unadjusted data [24,26], where patients with PCCD placement received a lower quantity of transfused blood or cryoprecipitates.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, one study found that with very low certainty of evidence, patients with a PCCD placement in pre-hospital setting could signi cantly receive less blood transfusions (OR 0.63, 95%CI 0.41-0.95). A similar nding was found in other two studies with unadjusted data [24,26], where patients with PCCD placement received a lower quantity of transfused blood or cryoprecipitates.…”
Section: Discussionsupporting
confidence: 88%
“…The included studies allowed the following comparisons: (i) PCCD placement vs. No PCCD; (ii) early PCCD placement vs. late placement following a radiological assessment. As for setting, three studies [20,24,25] evaluated the use of PCCD in the pre-hospital setting, three studies in Emergency Department (ED) [19,26,27] and four studies both in the pre-hospital and in ED settings [18, [21][22][23]. General characteristics are reported in Table 1.…”
Section: General Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations